1999
DOI: 10.1080/026404199365605
|View full text |Cite
|
Sign up to set email alerts
|

The quantification of joint laxity in dancers and gymnasts

Abstract: The aim of this study was to determine the range of movement in gymnastic and dance populations. Sixty-five participants (41 females, 24 males; mean age 21.4 years) were assessed. The sample included dancers and gymnasts ranging from novice and club standard to international and professional status. Non-specialized physical education students acted as controls. Range of movement was measured at the shoulders, hips, lumbar spine and ankles using a Loebl hydrogoniometer, and inherent joint laxity was assessed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
52
2
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 32 publications
3
52
2
4
Order By: Relevance
“…3 Joint mobility decreases with age, 4 and generalized hypermobility is more prevalent among women. 5,6 From a preliminary uncontrolled study, it was concluded that at least a subgroup (25%, 11/44) of adult patients with chronic fatigue syndrome (CFS) present with evidence of generalized joint hypermobility. 7 In another study, joint hypermobility was more common in children with CFS than in otherwise healthy children with common skin disorders.…”
mentioning
confidence: 99%
“…3 Joint mobility decreases with age, 4 and generalized hypermobility is more prevalent among women. 5,6 From a preliminary uncontrolled study, it was concluded that at least a subgroup (25%, 11/44) of adult patients with chronic fatigue syndrome (CFS) present with evidence of generalized joint hypermobility. 7 In another study, joint hypermobility was more common in children with CFS than in otherwise healthy children with common skin disorders.…”
mentioning
confidence: 99%
“…Joint mobility decreases with age (Seow et al, 1999), and generalized hypermobility is more prevalent among women compared to men (Rowe et al, 1999;Gannon and Bird, 1999). In addition, epidemiological studies have shown that prevalence rates of generalized hypermobility vary according to the ethnic background (Hudson et al, 1995;Grahame, 1999).…”
Section: Prevalencementioning
confidence: 97%
“…A recently published population-based twin study concluded that genetic factors have a substantial contribution to joint hypermobility in the adult female population . Generalized joint hypermobility is a very common finding in conditions of connective tissue abnormalities (EhlersDanlos syndrome, Marfan syndrome, and osteogenesis imperfecta) (Norton et al, 1995;Hakim and Grahame, 2003), and is more common in gymnasts and dancers than in nonspecialized physical education students (Gannon and Bird, 1999). Generalized joint hypermobility appears to be associated with anxiety disorders: 67 of 99 (67.7%) patients with panic disorders or agoraphobia were hypermobile, compared to 10 of 99 (10.1%) psychiatric control subjects (Po:001) (Martin-Santos et al, 1998).…”
Section: Prevalencementioning
confidence: 99%
“…En este sentido, se ha informado que cuando un deportista presenta los valores normales y específicos de flexibilidad en cada articulación de un determinado deporte, éste dispone de un ROM óptimo para favorecer el máximo rendimiento físico-técnico deportivo con una menor predisposición a la lesión deportiva (Riewald, 2004;Santana, 2004). Así, diversos trabajos han observado que el rendimiento deportivo declina tanto con el ROM extremo "hipermovilidad" (Gannon y Bird, 1999;Snyder, McLeod y Hartman, 2006) como con el ROM limitado por una menor extensibilidad muscular "cortedad muscular" (Young, Clothier, Otago, Bruce y Liddell, 2003;Rahnama, Lees y Bambaecichi, 2005;Zakas, Vergou, Zakas, Grammatikopoulou y Grammatikopoulou, 2002;Zakas, Vergou, Grammatikopoulou, Sentelidis y Vamvakoudis, 2003). Además, la cortedad muscular ha sido correlacionada con la lesión muscular (Bradley, Olsen y Portas, 2007;Dadebo, White y George, 2004;Ekstrand, Wiktorsson, Oberg y Gillquist, 1982;Rahnama et al, 2005;Witvrouw, Danneels, Asselman, D'Have y Cambier, 2003), la lesión ligamentosa como el esguince de tobillo (Ekstrand y cols., 1982;Pope, y cols., 1998; Okamura y cols., 2014) y la rotura del ligamento cruzado anterior (Ellera, Vieira y Becker, 2008), y la lesión por sobrecarga como la fascitis plantar, la tendinopatía rotuliana y aquilea, la periostitis tibial, el síndrome de la cintilla iliotibial y el síndrome de dolor femoropatelar (Witvrouw, Mahieu, Roosen y McNair, 2007;Probst, Fletcher y Seeling, 2007;Johanson, Baer, Hovermale y Phouthavong, 2008).…”
Section: Introductionunclassified
“…Esos valores han guiado a los profesionales del deporte y de la Salud para proporcionar un ROM articular y una función óptima en una articulación sana. Sin embargo, considerándose que el ROM es específico de cada deporte (Cejudo, Sainz de Baranda, Ayala y Santonja, 2014a,b;Gleim y McHugh, 1997), nivel competitivo (Battista, Pivarnik, Dummer, Sauer y Malina, 2007;Gannon y Bird, 1999;Haff, 2006), articulación, acción o movimiento (Hahn et al, 1999;Zakas et al, 2002;Hedrick, 2002), sexo (Canda, Heras y Gómez, 2004;Kibler y Chandler, 2003), segmento corporal (dominante y no dominante) (Chandler et al, 1990;Magnusson, Aagard, Simonsen y Bojsen-Moller, 1998;Probst et al, 2007) y puesto táctico (Cejudo, Sainz de Baranda, Ayala y Santonja, 2014a;Oberg, Ekstrand, Möller y Gillquist, 1984), aplicar este enfoque tradicional al deportista no permite definir el perfil óptimo de flexibilidad.…”
Section: Introductionunclassified